2019
DOI: 10.1093/fampra/cmz074
|View full text |Cite
|
Sign up to set email alerts
|

General practitioners’ practical approach to initiating end-of-life conversations: a qualitative study

Abstract: Background As doctors who provide care across the life-course, general practitioners (GPs) play a key role in initiating timely end-of-life discussions. Nonetheless, these discussions are often not initiated until close to death. Given the ageing of the population, GPs will be confronted with end-of-life care more often, and this needs to become a core skill for all GPs. Objective To describe GPs’ approach to initiating end-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…These findings indicate the importance of providing GPs and their patients in RACFs with the opportunity to discuss end-oflife issues. This may require policies and practices to support greater communication between GPs and both patients and staff at RACFs (Balmer et al, 2020;Deckx et al, 2019;Thomas et al, 2019).…”
Section: Ta B L E 1 Characteristics Of Participating Gpsmentioning
confidence: 99%
“…These findings indicate the importance of providing GPs and their patients in RACFs with the opportunity to discuss end-oflife issues. This may require policies and practices to support greater communication between GPs and both patients and staff at RACFs (Balmer et al, 2020;Deckx et al, 2019;Thomas et al, 2019).…”
Section: Ta B L E 1 Characteristics Of Participating Gpsmentioning
confidence: 99%
“…The qualitative analysis of the focus groups showed that PCPs felt empowered to take an active role in the follow-up of their patients during oncologic treatment. As described in the literature, PCPs felt responsible to initiate end-of-life discussions, arising from their role and expertise, and these conversations' bene ts (23,24). PCPs felt better equipped in communication skills, and picked up cues more easily to address advance directives or end-of-life discussions, having practiced in role plays and made their own experience with patients.…”
Section: ) Discussionmentioning
confidence: 99%
“…The qualitative analysis of the focus groups showed that PCPs felt empowered to take an active role in the follow-up of their patients during oncologic treatment. As described in the literature, PCPs felt responsible to initiate end-of-life discussions, arising from their role and expertise, and these conversations’ benefits [ 25 , 26 ]. PCPs felt better equipped in communication skills, and picked up cues more easily to address advance directives or end-of-life discussions, having practiced in role plays and made their own experience with patients.…”
Section: Discussionmentioning
confidence: 99%